Are feature assignment errors due to attraction? The case of Bulgarian numeral phrase - Khristov, Danil; Stateva, Penka; Franck, Julie; György, Dávid; Stepanov, Arthur (Frontiers in Psychology, 2025)
Well-studied attraction errors in speakers' production of subject-verb agreement arise from featural similarity between the attractor and the target (e. g., the verb) in the context of a specific syntactic relationship characterized by structural distance. This study examines production errors in a related but distinct type of featural manipulation: feature assignment in numeral phrases with modifiers such as “five rusty old windows,” in Bulgarian. The grammar of this language requires plural markers on the modifiers and a morphological count form on the final noun which speakers often erroneously replace with a regular plural form. In a series of four sentence completion experiments we demonstrate that speakers' errors in count form assignment are subject to linear rather than structural distance. Based on this, we argue that these errors are not due to attraction but instead reflect the cost of temporary storage and integration to resolve the assignment dependency, thus supporting linear distance-based theories of processing locality. Our findings also point to potential differences in the processing dynamics between agreement and feature assignment.